Domino free radical photopolymerization based on phototriggered base proliferation reaction and redox initiation. Issue 11 (21st March 2014) - He, Minghui; Jiang, Shun; Xu, Ruixin; Yang, Jianwen; Zeng, Zhaohua; Chen, Guangxue
ABSTRACT: A detailed evaluation of the kinetics of domino free radical photopolymerization (DFRP) based on phototriggered base proliferation reaction and redox initiation was described in the condition of eliminating the heat of polymerization via reacting in the thin polymer films. First, domino photoinitiating system made a substantial breakthrough in the photoefficiency of amine generation in contrast to photocaged base system, exhibiting marked improvement in the photosensitivity. Second, both the structural feature of base amplifier (BA) and reaction temperature as two important factors impacting the proliferation rate have been detailed. Third, different domino photoinitiating components, such as BAs, peroxides, and acrylates, were investigated in the thin polymer films. It is shown that both primary and secondary BAs are efficient catalysts for DFRP. Furthermore, polymerization rate shows a consistent dependence on the p K a value of the proliferated amine. Finally, remarkable post conversion after irradiation was achieved in DFRP. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 1560–1569 Abstract : A detailed evaluation of the kinetics of domino free radical photopolymerization based on phototriggered base proliferation reaction and redox initiation in the thin polymer films is described.